COMPARING CARCASS END-POINT AND PROFIT MAXIMIZATION DECISION RULES USING DYNAMIC NONLINEAR GROWTH FUNCTIONS — CORRIGENDUM. (18th March 2015) - MAPLES, JOSHUA G.; COATNEY, KALYN T.; RILEY, JOHN M.; KARISCH, BRANDI B.; PARISH, JANE A.; VANN, RHONDA C.
<x content-type="archive" xml:space="preserve">Abstract</x> In the Journal of Agricultural and Applied Economics Volume 47 (Number 1), Equations 7 and 10 were published with errors.